Comparative thermal ecology of copperheads (Agkistrodon contortrix) and cottonmouths (Agkistrodon piscivorus). (January 2019) - Mueller, Andy; Gienger, C.M.
Highlights: Copperheads and cottonmouths have nearly identical preferred body temperatures. Cottonmouths maintain a higher body temperature in May and June. Cottonmouths thermoregulate more effectively than copperheads in May, June, and July. Copperheads and cottonmouths exploit their thermal environments similarly.